Ministry Of Finance Decree No. 379 Of The Year 2018 Amending the Minister of Finance Decree No. 534 of the Year 2005 Concerning The Percentage to be Collected Out Of The Value of Imports for Account of the Tax From The Private Law Persons According To The Provision Of Article (67) Of Income Tax Law No. 91 Of The Year 2005 = وزارة المالية قرار رقم 379 لسنة 2018 بتعديل قرار وزير المالية رقم 534 لسنة 2005 بشأن النسبة التى تحصل من قسمة الواردات تحت حساب الضريبة من أشخاص القانون الخاص طبقاً لحكم المادة (67) من قانون الضريبة على الدخل رقم 91 لسنة 2005 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic